Collagen 3D matrices as a model for the study of cell behavior in pulmonary fibrosis. (16th March 2022) - Machahua, Carlos; Vicens-Zygmunt, Vanesa; Ríos-Martín, Jesús; Llatjós, Roger; Escobar-Campuzano, Ignacio; Molina-Molina, María; Montes-Worboys, Ana
Abstract: Purpose: Idiopathic pulmonary fibrosis (IPF) is a complex progressive chronic lung disease where epithelial to mesenchymal interaction, extracellular matrix (ECM) contact, and pro-fibrotic cytokines dynamics take part in the development of the disease. The study of IPF in the widespread in vitro two-dimensional (2 D) culture fails to explain the interaction of cells with the changing environment that occurs in fibrotic lung tissue. A three-dimensional (3 D) co-culture model might shed light on the pathogenesis of IPF by mimicking the fibrotic environment. Materials and Methods: Fibroblasts from nine IPF were isolated and embedded in collagen matrices with the alveolar epithelial human cell line (A549) on the top. Cells were also cultured in 2 D with and without TGF-β1 as a conventional model to compare with. Both types of cells were isolated separately. Protein and gene expression of the main fibrotic markers were measured by qPCR, Western blot, and ELISA. Results: IPF fibroblasts to myofibroblasts differentiation was observed in the 3 D model and in cells stimulated with TGF-β1. In addition, ECM-related genes were highly up-regulated in the 3 D collagen matrix. A549 co-cultured 3 D with IPF fibroblasts showed EMT activation, with down-regulation of E-cadherin (CDH1). However, other pro-fibrotic genes as VIM, TGFB1, and MMP7 were up-regulated in A549 co-cultured 3 D with fibroblasts. Conclusions: 3 D-collagen matrices might induce fibroblasts' fibrotic phenotype as in the classic TGF-β1 model, by up-regulating genes associated with matrix production. In addition, IPF lung fibroblasts seem to exert a pro-fibrotic influence in A549 cells when they are co-cultured. These results suggest that an improved 3 D co-culture model might serve as an important tool to study the fibrotic process and its regulation.